DEIXIS ANALYSIS IN THE SHORT STORY TITLED “LITTE BO-PEEP” BY JOSEPH MARTIN KRONHEIM - Jauza Fatin Nabillah (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
Deixis is a word or phrase that refers to a place, time, or situation based on the context of a conversation. Deixis is expressed in English using personal pronouns, demonstratives, adverbs, and tenses. There are three types of deixis, they are personal deixis, time deixis, and place deixis. This study aims to analyze and find out the deixis used in the short story titled 'Little Bo-Peep' written by Joseph Martin Kronheim. The method used in this research is a descriptive qualitative method because it analyzes the types of deixis used in the short story. The steps to analyze data are, read the short story, find deixis in the short story, analyze the deixis, and classify the types of deixis used in the short story. The results showed that there were three types of deixis, they are personal deixis, time deixis, and place deixis. The most commonly used deixis in this short story is personal deixis because there is a total number of 126 (85.7%). Keywords: Deixis, short story, Little Bo-Peep